Determinants of Indonesian Sugar Import - Inayaturrohmah, Winni Putri; Istiqomah, Istiqomah; Gunawan, Ratna Setyawati (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Indonesian sugar imports have increased due to a steady increase in sugar consumption, while domestic sugar output has increased but has not kept pace with consumption. This study aims to examine the impact of sugar consumption, income per capita, sugarcane harvested area, and sugarcane productivity on sugar imports in Indonesia. The data in this study include time series data from 1995 to 2021 that were analyzed using multiple regression. Sugar consumption and income per capita have a statistically significant positive effect on sugar import, whereas sugarcane harvested area and sugarcane productivity significantly negatively affect sugar import. Several policy options for reducing sugar imports are recommended, including reducing sugar consumption through education and healthy lifestyle programs, extending sugarcane-harvested areas, and rejuvenating and building new sugar mill.JEL Classification: F14, C22How to Cite:Inayaturrohmah, W. P., Istiqomah & Gunawan, R.S. (2023). Determinant of Sugar Import. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 275-286. https://doi.org/10.15408/sjie.v12i2.28044.